The U.S. Monetary System : Money, Banking, and Financial Markets - Hamberg, Daniel (Boston : Little, Brown, 1981)
This book has one over-riding objective: To make clear to students of money and banking the way in which our monetary system actually functions.
Includes bibliographies and index.
osc 16/8/17
Loans
Keywords: Money; Money market; Banks and Banking; Finance